Analisis Pengawasan Pemungutan Pajak Reklame Pada Unit Pelayanan Pajak Daerah Kecamatan Cilincing Kota Administrasi Jakarta Utara Tahun 2021 - Uli, Olivia Risma; Hartono, Hartono; Andrayanti, Iin (Jurnal Ilmu Administrasi Publik, 2024)
The phenomenon in this study is the low awareness of taxpayers to pay off the amount of tax owed themselves, the tax sanctions given are too low for taxpayers or companies that commit violations, lack of human resources or officers from the Cilincing District UPPD who carry out supervision compared to the number of billboards issued. scattered in the Cilincing sub-district area and many billboards that have not been re-registered. This study aims to identify and analyze supervision, obstacles encountered and efforts that can be made regarding supervision of advertisement tax collection at UPPD Cilincing District, North Jakarta. The research method used is qualitative method and the type of research is descriptive. The results of this study are to set standards in its application to oversight of billboard tax collection that has been running in accordance with the SOP, measuring the performance of oversight of collection carried out by UPPD has not been effective due to limited human resources for supervision, to compare performance with this standard, oversight of billboard tax collection has been carried out by UPPD in accordance with the SOP, namely advertisement licensing procedures, taxpayer registration, tax determination and calculation, collection and write-off of tax receivables, objections, appeals, supervision, control of advertisements and determining the need for corrective action for UPPD officers of Cilincing District must provide strict sanctions in the form of dismantling inappropriate advertisements provision. The obstacles faced are the lack of taxpayer compliance, limited human resources, namely only having 3 inadequate personnel, and the lack of public knowledge about the procedures for implementing billboards. Efforts have been made to further increase information and socialization to the public, form a special team to supervise advertisement tax and impose strict sanctions in the form of increasing administrative fines, which are currently quite low at 2%to make supervision carried out more optimally.